Spatial-temporal changes of land use/cover change and habitat quality in Sanjiang plain from 1985 to 2017 - Jin, Shanhe; Liu, Xin; Yang, Jiajia; Lv, Junchao; Gu, Yuchao; Yan, Jishun; Yuan, Ruiyang; Shi, Yudi (Frontiers in Environmental Science, 2022)
Land use/Land cover (LULC) change seriously affects ecosystem services and ecosystem functions. In order to maintain ecological security and orderly social development, habitat quality assessment based on LULC change is worth exploring. Based on multi-source land use data and Google remote sensing data from 1985 to 2017, land use transfer matrix and habitat quality index were used to study land use change, spatial-temporal evolution of habitat quality, and driving factors influencing habitat quality change in Sanjiang Plain. The results showed that land use/cover changed significantly from 1985 to 2017, especially paddy land increased by 22184.92 km2, while unused land decreased by 11533.53 km2. The increase of urban and rural land, industrial land and residential land was mainly at the expense of dry land. There was a polarization in habitat quality, and the high intensity of land use utilization and development resulted in a significant decrease in habitat quality. From 1985 to 2017, the largest change in habitat quality was grassland, which decreased from 0.99 to 0.91.